Nutrient intake from food frequency questionnaire compared to 24-hour recall and blood lipids among individuals aged 15 years and above (2007)
This study compared nutrient intake from food frequency questionnaire (FFQ) to that from 24-hour recall among 1,419 individuals and examined the agreement between the two methods. It also examined the relationship between nutrient intake and blood lipids. Results showed that intake were significantly lower using FFQ than the 24-hour recall. Percent agreement of intake in the same and next higher or lower quantile were 41.5% and 78.5%, respectively, for energy; 34.2% and 73.6% for protein; 45% and 85.5% for carbohydrates; 31.6% and 72.8% for fat; 29.5% and 64.4% for cholesterol; and 19.4% and 52.2% for fiber. The measure of agreement between two methods using kappa values were significant for energy, protein, fat, carbohydrates, and cholesterol, but not for fiber intake. Blood cholesterol correlated inversely with protein and fat in the FFQ. Low density lipoprotein was inversely correlated with protein and fat. Using 24-hour food recall, dietary cholesterol correlated inversely with triglycerides. Intake from FFQ underestimates that of 24-hour recall, but FFQ may be used to rank individuals into high or low intake. The ability of FFQ to predict risk using blood lipids is limited.
Keywords: Nutrition surveys